1999
DOI: 10.5511/plantbiotechnology.16.225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Chromosome-doubled Regenerates with Resistance to Potato Tuber Moth (Phthorimaea opercullella (Zeler)).

Abstract: In vitro chromosome doubling by the use of the variation induced by zeatin riboside was applied to generate tetraploid individuals to introgress potato tuber moth (PTM) resistance from diploids to tetraploids. This approach is especially important when the expression of desirable traits is strongly influenced by cytoplasmic factors. The levels of PTM resistance and yield performance was evaluated in chromosome-doubled regenerates and their corresponding original diploids. The levels of PTM resistance were main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The second phase is that shoots form, the callus was changed into the MSA medium (CIP-Centro Internacional de la Papa-International Potato Center): Murashige Minimal Organic Medium with a low concentration of GA3 and sucrose. Interestingly, these tetraploid potatoes are more likely to be resistant to potato tuber moths [12,37,38] . In micropropagation of tomato (Solanum lycopersicum) induced by IAA and zeatin, the frequency of polyploid found ranging 9%-14% is an apparent example [39] .…”
Section: Achievements Of Polyploidization Through Plant Growth Regula...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second phase is that shoots form, the callus was changed into the MSA medium (CIP-Centro Internacional de la Papa-International Potato Center): Murashige Minimal Organic Medium with a low concentration of GA3 and sucrose. Interestingly, these tetraploid potatoes are more likely to be resistant to potato tuber moths [12,37,38] . In micropropagation of tomato (Solanum lycopersicum) induced by IAA and zeatin, the frequency of polyploid found ranging 9%-14% is an apparent example [39] .…”
Section: Achievements Of Polyploidization Through Plant Growth Regula...mentioning
confidence: 99%
“…However, using antimitotic chemicals might make a high ratio of chimera plants which reached 50%-100% by treating oryzalin [8,10] . In contrast, the method of phytohormone induction that can make euploidy plants with chromosomes doubling by phytohormone-based induction to be substantially successful [11,12] will be deeply discussed here. Although studies showed that residues of phytohormones when using in production or in the field can affect environmental pollution, the development of animal, human health problems, and food poisoning if using them was not corrected the producer's instruction [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…The ploidy level of the original diploid plant and tetraploid plants was confirmed by chromosome count. Root tips were excised and collected from in vitro plants to chromosome counting according to a method previously described by Watanabe et al (1999). The samples were then immersed in 0.5% (w/v) colchicine solution for 6 h. After washing with distilled water, the root tips were treated with 1 N hydrochloric acid (HCl), incubated at 60 °C for 8 min.…”
Section: Chromosome Countingmentioning
confidence: 99%
“…Among them, Mexican S. bulbocastanum and S. cardiophyllum may represent a useful source of noteworthy genes. Resistance to a number of pests and diseases has been reported by Watanabe et al (1999), Bamberg et al (1994), andChen et al (2003). Due to post-zygotic incompatibility isolation mechanisms, these species have not been used extensively in potato breeding.…”
Section: Introductionmentioning
confidence: 95%